2021
DOI: 10.3390/s21237780
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Validation of Real-Time Ski Jumping Tracking System Based on Wearable Sensors

Abstract: For sports scientists and coaches, its crucial to have reliable tracking systems to improve athletes. Therefore, this study aimed to examine the validity of a wearable real-time tracking system (WRRTS) for the quantification of ski jumping. The tracking system consists of wearable trackers attached to the ski bindings of the athletes and fixed antennas next to the jumping hill. To determine the accuracy and precision of the WRRTS, four athletes of the German A or B National Team performed 35 measured ski jumps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The dataset covers a wide range of jump lengths and athletes, which leads to good prediction accuracy over jump lengths and generalization over athletes. Even though the dataset has the largest number of different ski jumping venues and athletes used in a tracking study [ 21 , 31 , 33 , 40 , 41 , 42 , 43 , 44 ], the number of venues is relatively small and unevenly distributed compared to the number of athletes. This could be improved in the future.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The dataset covers a wide range of jump lengths and athletes, which leads to good prediction accuracy over jump lengths and generalization over athletes. Even though the dataset has the largest number of different ski jumping venues and athletes used in a tracking study [ 21 , 31 , 33 , 40 , 41 , 42 , 43 , 44 ], the number of venues is relatively small and unevenly distributed compared to the number of athletes. This could be improved in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The jump length within our dataset, which is the regression goal, is determined with the WRTTS and not the manually labeled video distance as in official competitions. Nevertheless, in a previous study, we showed that the jump length determined by the WRTTS and the official video distance differ by [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, researchers have used computational fluid dynamic simulations and wind tunnel measurements, and there have been a small number of studies using video analysis to examine how the glide posture can influence glide parameters, such as the aerodynamic relationship between the lift (F L ) and drag forces (F D ), i.e., LD-ratio [9,[13][14][15][16][17][18][19]. In recent years, wearable sensors as inertial measurement units (IMUs) have shown promising results when measuring kinematics and kinetics from the start of the inrun to the landing [20][21][22][23][24][25][26][27][28]. A suitable method used to provide accurate field data from the steady glide phase is differential global navigation satellite system (dGNSS) technology.…”
Section: Introductionmentioning
confidence: 99%